2022
DOI: 10.1177/08465371221083970
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Association of Radiologists Guidance on Contrast Associated Acute Kidney Injury

Abstract: Iodinated contrast media (ICM) is one of the most frequently administered pharmaceuticals. In Canada, over 5.4 million computed tomography (CT) examinations were performed in 2019, of which 50% were contrast enhanced. Acute kidney injury (AKI) occurring after ICM administration was historically considered a common iatrogenic complication which was managed by screening patients, prophylactic strategies, and follow up evaluation of renal function. The Canadian Association of Radiologists (CAR) initially publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 58 publications
(83 reference statements)
2
31
0
Order By: Relevance
“…In fact, from our results, iodinated CM was more frequently involved in a major number of ICSRs, and serious ADRs, resulting in a more probable relationship with drug-adverse events according to the applied Naranjo algorithm. In the last years, attention has been given to CM nephrotoxicity among organ-specific adverse reactions, probably caused by induced endothelial dysfunction and renal cell apoptosis [ 21 , 45 ]. However, in our period study, renal disorders did not emerge as frequently, and only a few cases reported nephropathies or renal disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, from our results, iodinated CM was more frequently involved in a major number of ICSRs, and serious ADRs, resulting in a more probable relationship with drug-adverse events according to the applied Naranjo algorithm. In the last years, attention has been given to CM nephrotoxicity among organ-specific adverse reactions, probably caused by induced endothelial dysfunction and renal cell apoptosis [ 21 , 45 ]. However, in our period study, renal disorders did not emerge as frequently, and only a few cases reported nephropathies or renal disorders.…”
Section: Discussionmentioning
confidence: 99%
“…IHC was defined by any new infection different from wound infection, new cardiovascular events including cerebral and myocardial ischaemia, acute renal injury due to contrast induced nephropathy (CIN), onset of severe anaemia (hb < 8 gr/dL) requiring blood transfusion, and any new other clinical or surgical problem not present at the assessment. CIN was considered as the increase creatinine values of 0.5 mg/dL or 25% from baseline in 48–72 h after the contrast media administration 15 . Major amputation was considered any amputation above‐the‐ankle.…”
Section: Methodsmentioning
confidence: 99%
“…CIN was considered as the increase creatinine values of 0.5 mg/dL or 25% from baseline in 48-72 h after the contrast media administration. 15 Major amputation was considered any amputation above-the-ankle.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Iodinated contrast agent is the main media of contrast-induced nephropathy, and its osmotic pressure is one of the influencing factors. Studies have confirmed that the risk of CI-AKI is lower in high-osmolar contrast than in low-osmolar contrast, but there is no significant difference between iso-osmolar contrast and low-osmolar contrast [ 91 , 92 ].…”
Section: Theories Of Csa-aki Pathophysiologymentioning
confidence: 99%